Does tackling form affect head acceleration in youth football players?. (September 2020) - Gellner, Ryan A; Campolettano, Eamon T; Rowson, Steven
To reduce head impact exposure, a number of youth football organizations have begun teaching tackling technique. This study sought to develop and utilize a set of tackling form grading criteria for both tacklers and ball carriers as well as to relate tackling form to head acceleration outcome. It was hypothesized that players exhibiting better form would experience lower head accelerations in individual tackles. Three teams consisting of 67 players (20, 29, and 18 players per team; age 12.7 ± 0.95, age range 11–14 years, body mass 55.1 ± 16.2 kg) were instrumented with helmet-mounted accelerometer arrays for one season. Videos of close-range tackling drills were used to develop tackling form criteria. Two raters used these criteria to each score 105 impacts. Six of the seven categories were found to have good inter-rater reliability metrics (total percent agreement ≥ 79%, agreement coefficient ≥ 0.65). Bending at both the hips and knees, leading with the shoulder or arm, and initiating contact were found to reduce risk of high-magnitude (>40 g) head impacts in tacklers. Keeping the eyes up and avoiding dropping the head reduced the risk of high-magnitude head impacts in ball carriers. This study shows the potential effectiveness of training both tacklers and ball carriers in proper technique for collisions in youth football to minimize head impacts.